Towards the Knowledge-Smart Professional Service Firms: How High-Performance Work Systems Support the Transformation - Rehman, Junaid; Hawryszkiewycz, Igor; Sohaib, Osama; Namisango, Fatuma; Dahri, Abdul Samad (Journal of the knowledge economy, 2023)
The Professional Service Firms (PSFs) have gained widespread attention owing to their enormous contribution to the growth of global service economies. PSFs being knowledge-intensive firms frequently encounter a challenge of continually enhancing the knowledge competencies of their staff that forms the basis of organizational Intellectual Capital (IC) and derives competitive advantage for them. Nevertheless, a little research has been done governing the development of knowledge capital in the PSFs. This makes the role of High Performance Work Systems (HPWS) indispensible towards managing intellectual capital resources in these firms. However, the systematic application of HPWS in PSF context is still lacking the empirical basis. Therefore, by presenting a qualitative conceptual framework, this research offers a linking mechanism on how HPWS guide IC development in the service firms. By empirically testing these HPWS as (Ability, Motivation, and Opportunity)-enhancing practices via face-face interviews, the results demonstrate that HPWS play strategically significant role in building knowledge capital in the PSFs. Overall, this research offers practical insights to the KM and HR managers in service firms on achieving client service quality and satisfaction through a knowledge-smart workforce and perpetuate a sustainable competitive advantage.